New Insights Into the Pathologic Roles of the Platelet-Activating Factor System - Travers, Jeffrey B.; Rohan, Joyce G.; Sahu, Ravi P. (Frontiers in Endocrinology, 2021)
1 Described almost 50 years ago, the glycerophosphocholine lipid mediator Platelet-activating factor (PAF) has been implicated in many pathologic processes. Indeed, elevated levels of PAF can be measured in response to almost every type of pathology involving inflammation and cell damage/death. In this review, we provide evidence for PAF involvement in pathologic processes, with focus on cancer, the nervous system, and in photobiology. Importantly, recent insights into how PAF can generate and travel via bioactive extracellular vesicles such as microvesicle particles (MVP) are presented. What appears to be emerging from diverse pathologies in different organ systems is a common theme where pro-oxidative stressors generate oxidized glycerophosphocholines with PAF agonistic effects, which then trigger more enzymatic PAF synthesis via the PAF receptor. A downstream consequence of PAF receptor activation is the generation and release of MVP which provide a mechanism to transmit PAF as well as other bioactive agents. The knowledge gaps which when addressed could result in novel therapeutic strategies are also discussed. Taken together, an enhanced understanding of the PAF family of lipid mediators is essential in our improved comprehension of the relationship amongst the diverse cutaneous, cancerous, neurologic and systemic pathologic processes.